Risk factors for axillary lymph node metastasis in breast cancer (Annals of Medical Research, 2021)
Aim: As well as in Turkey as in the rest of the World, breast cancer is an increasing health problem. Although the axillary lymph node dissection is seen as an integral part in the breast cancer treatment, for it provides staging and local control, it also leads to complications and morbidity.
Keywords: Breast cancer; lymph node; risk factors.